Relationship Of The Nurse's Work Environment With Patient Safety At Sejati Medan Partner General Hospital - Sontina Saragih; Trionyta Debora; Liani Br Ginting; Dian (Institute of Computer Science (IOCS), 2022)
Objective: Assurance of patient safety to realize the quality of health services is the responsibility of all health workers, especially nurses. Improving patient safety can reduce the risk of nosocomial infections and prevent the negative effects of nursing actions. The application of patient safety is still low due to several aspects, namely communication errors (57.7%), safety and service quality (57.4%), open communication (54.4%), management support (53.8%), and the work environment. (28.4%). An unfavorable work environment for the professional practice of nursing harms the quality of nursing care and patient safety. Methods: Analyzed the relationship between the nurse's work environment and patient safety at Mitra Sejati General Hospital, Medan. Methods: This research is a correlational analytic descriptive study with a cross-sectional approach. The study population was all nurses in the inpatient room at Mitra Sejati General Hospital, Medan, totaling 200 nurses. The sampling technique used was total sampling, by setting inclusion criteria. The study wascarried out from March to July 2022. Data analysis was carried out univariate and bivariate using the chi-square test. Results: most of the respondents stated that patient safety was well implemented (56%) and the work environment was good (64.5%). There is a significant relationship between the nurse's work environment and patient safety, p-value = 0.005. Conclusion: A good working environment for nurses ensures the optimal implementation of patient safety. Therefore, the hospital management contributes to supporting a conducive working environment for nurses by involving nurses in decision-making related to the development of nursing services, improving the ability of nurses, fulfilling nurse resources according to the required expertise